Juridical Review of Legal Smuggling on the Transfer of Land Ownership Rights Between Foreigners and Foreigners (Case Study of Decision Number: 274/Pdt.G/2020/PN.Dps) - Fauzan Ghafur (JUSTICES: Journal of Law, 2025)
In Indonesia, land regulations are regulated in the Basic Agrarian Law (UUPA) No. 5 of 1960, where the UUPA regulates the prohibition of land ownership rights for foreign citizens. The prohibition of ownership rights for foreign citizens is regulated in Article 21 of the UUPA, in accordance with one of the principles of agrarian law, namely the principle of nationality. This paper will examine the Denpasar District Court Decision Number 274 / Pdt.G / 2020 / PN Dps where there is ownership of land rights by foreign citizens. This study uses a normative legal research method with a statutory approach and an analytical approach. The technique of collecting legal materials through document studies, then the collected legal materials are analyzed using descriptive techniques equipped with a qualitative approach. The results of this study are that the Notarial Deed containing the transfer of land ownership rights from Indonesian citizens to foreign citizens is null and void and for this the Notary can be held accountable.